MEDICAL STUDIES AS A FACTOR IN SEASIDE RESORTS DEVELOPMENT IN THE UK IN THE XIX CENTURY - D. V. Antoshuk (Гуманитарные и юридические исследования)
The paper features the analysis of early medical studies of UK coastal zone climate. The author focuses on such aspects as the healing properties of water, air and other natural elements of the seaside. The paper demonstrates the data of medical surveys on the impact of climatic factors on treatment of certain diseases. These data determined the therapeutic specialization of the seaside areas. The author concludes that medical studies had decisive inluence on the development of the UK seaside resorts in the XIX century.